User group based multi-satellite handover strategy for LEO satellite networks - Hongtao ZHU; Qing GUO (Dianxin kexue)
LEO satellite network plays an important role in global communication in the future mobile communication.In large-scale LEO satellite networks, frequent concurrent handoffs by a large number of users will reduce the handover success rate and increase the signaling overhead.In order to solve this problem, a multi satellite handover strategy based on user group for LEO satellite networks was proposed.When triggering the handover, the user will send the candidate handover satellites that meet its own communication needs to the access satellite.The access satellite groups users considered the conditions of user handover success rate, satellite throughput rate and satellite load balancing to complete the whole handover process.A signaling interaction process of handover strategy based on user group was designed, and the signaling overhead of group handover was analyzed.The simulation results show that the multi-satellite handover strategy of LEO satellite network based on user group can effectively reduce the transmission of network repeated signaling and reduce the system signaling overhead.At the same time, it can effectively improve the user handover success rate and satellite throughput, and balance the satellite network load.